Fiscal Consolidation and the Current Account: OECD Evidence - Christian Breuer; Chang Woon Nam (Center for Economic Studies and ifo Institute (CESifo), 2020)
We apply a "new" conventional (CAPB-based) measure of fiscal policy, which is less prone to endogeneity issues, and find that a 1-percent of GDP fiscal consolidation leads to the improvement of the current account-to-GDP ratio by approximately 0.8 percent of GDP, while previous research based on conventional measures found a relationship of only 0.1-0.3 percentage points. We suggest that previous results based on conventional measures are biased towards underestimating the twin-deficit linkage because of endogeneity issues and the failure to adjust the CAPB for cyclical effects. After adjustment, the twin-deficit effect is particularly pronounced in the case of expenditure cuts and in Eurozone countries. These findings are in line with previous evidence based on narrative measures.
Keywords: E62; E63; H50; 330; fiscal adjustment; current account; twin deficit; Eurozone countries